Awareness on mass hysteria among public school teachers of Makwanpur district. - Sherpa,Jangmu (2020)
ABSTRACT: Background: Mass hysteria is the spontaneous outbreak of atypical thoughts, feelings, or actions in a group or social aggregate. Manifestations may include psychogenic illness, collective hallucinations, and bizarre actions. Mass hysteria is also described as "mass conversion disorder" or "mass psychogenic illness". The study was done to assess the awareness level of public school teachers regarding mass hysteria and the association of awareness level and independent variables. Methodology: A descriptive cross-sectional study was conducted in public schools of Hetauda sub-metropolitan city of Makwanpur district. Representative sample was selected using cluster sampling technique and the sample size was 267. A selfadministered structured questionnaire was administered and data was analyzed using SPSS software. Results: The findings revealed that 46.8% teachers still had inadequate awareness on mass hysteria. There was association between the awareness level and gender of the teacher, teaching level, past experience of the teacher and knowledge of index case management. The male teachers were 2.2 times more aware than female teachers. Higher secondary level teachers were 13.6 times more aware than primary level teachers. The teachers experienced of dealing a mass hysteria incident were 5.9 times more aware in comparison to inexperienced teachers. And the teachers who had knowledge of index case management were 2.8 times more aware than teachers who had no knowledge of index case management. Conclusion: The findings of the study show that the teachers still have inadequate awareness on mass hysteria. Awareness level is associated with the gender of the teacher, teaching level, past experience of the teacher, and the teacher's knowledge on index case management. Keywords: Mass hysteria, awareness, teachers